Flexible and highly transparent two-component organogels with enhanced viscoelasticity for self-healing materials and room-temperature phase-selective gelation. Issue 97 (15th November 2016) - Liu, Jiahui; Li, Jingjing; Lin, Peng; Zhang, Nanxiang; Han, Xiaoyu; Zhang, Bao; Song, Jian
Abstract : Flexible and highly transparent two-component organogels with enhanced viscoelasticity showed excellent multi-functions. Abstract : A novel two-component organogel system based on acid–base interaction showed flexibility, high-transparency and self-healing properties with enhanced viscoelasticity. Meanwhile, the two-component gelator displayed room-temperature phase selective gelation of aromatic solvents from aromatic solvents/water mixtures in powder form and excellent dye removal ability.